Waiting for a New Leader ahead of the 2024 Presidential Election: Reflection of Indonesian Political History - Muhamad Husein Maruapey; Tora Akadira (Universitas Sultan Ageng Tirtayasa, 2022)
The article entitled Waiting for a New Leader Ahead of the 2024 Presidential Election (Reflection on 76 Years of Independence from a Cultural Perspective) is a study of constructive thinking about the political rights of citizens of all ethnic groups in Indonesia to hold power. power in our beloved Republic. Through qualitative research methods with descriptive analysis approach, positive responses from informants through structured and systematic interviews and supporting literature can explain the phenomenon under study. The results obtained through the research show that the government and related state institutions respond to the political rights of citizens to assume the position of President based on the mechanism of democratic principles and rules in accordance with Pancasila and the 1945 Constitution. The constitution and ideals of the Proclamation of National Independence by looking at the figure of a candidate for leader without distinction of race , ethnicity and culture